2011
DOI: 10.4322/floram.2011.049
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades da Madeira de Eucalyptus umbra R. T. Baker em Função do Diâmetro e da Posição Radial na Tora

Abstract: RESUMONeste trabalho, investigou-se a variação da densidade básica, dos constituintes químicos e das características anatômicas em função da classe de diâmetro (superior, mediana e inferior) e posição radial nas árvores de uma população de Eucalyptus umbra, de 25 anos de idade. Apenas o comprimento das fibras variou entre as classes de diâmetro. Fibras mais longas ocorreram na classe superior e fibras mais curtas, na classe inferior. Os resultados mostram a homogeneidade da madeira entre as classes de diâmetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
1
8
0
3
Order By: Relevance
“…Eucalyptus umbra is a species from Australia, with little diametric, Specific gravity, chemical constituents and anatomical characteristics variabilities [17]. In addition, Eucalyptus umbra is resistant to attack by bio-deterioration agents [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eucalyptus umbra is a species from Australia, with little diametric, Specific gravity, chemical constituents and anatomical characteristics variabilities [17]. In addition, Eucalyptus umbra is resistant to attack by bio-deterioration agents [18].…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus umbra wood presented higher density and lower f c0 and f M values compared to hybrid Eucalyptus urophylla x Eucalyptus grandis. Physical and mechanical properties of Eucalyptus umbra wood at 12% and 30% moisture contentsLima et al (2011) [17] evaluated for 25 years-old Eucalyptus umbra trees from a forest area at Piracicaba city, in Sao Paulo State, ρ ap 0.621 g/cm 3 (12% moisture content).…”
mentioning
confidence: 99%
“…For the tree diameter class of 8.1 cm, the highest value was in the intermediate zone, but there was no statistical difference between the radial sampled areas. In general, the increment trend is evidenced by the wall thickness of the fiber considering the pith to bark direction, corroborating the variation commonly found in the wood fibers of the Eucalyptus spp., in which some authors have found an increase in it (Evangelista et al, 2010;Lima et al, 2011;Ramos et al, 2011;Sette et al, 2009;Silva et al, 2007).…”
Section: Fibers Dimensions Of Charcoalmentioning
confidence: 98%
“…No Brasil, estudos dessa natureza são predominantes para as espécies dos gêneros Eucalyptus e Pinus. No entanto, pesquisas relacionadas às espécies nativas vêm crescendo, como exemplo destacam-se os trabalhos de Longui et al (2010); Lima et al (2011a); Valente et al (2013); Delucis et al (2013).…”
Section: Introductionunclassified